Need of Guidance for Resolving Psychological Problems of Secondary School Students; a Study in Pakistan - Karim, Rabia A.; Usman, Muhammad (Advances in Social Sciences Research Journal, 2016)
Guidance is a process which provides help to a person at every walk of his life. It is not a new concept; it is as old as man himself. Guidance is not the solution itself but a help to overcome and solve an individual’s problem. Although guidance is necessary at every stage and in any sphere of human life but its need crucially increases at secondary school level due to the sensitive age of students at this level that is extremely precious from educational point of view. Research includes an exclusive work on the need guidance at secondary school level. The result good progress, personality development, adjustment and goal achievement of students. This study is descriptive in nature consisting on data of 300 teachers and students of government school in Pakistan each. Findings have supported the need of guidance in schools.